CuCr2O4@rGO Nanocomposites as High-Performance Cathode Catalyst for Rechargeable Lithium–Oxygen Batteries - Liu, Jiandi; Zhao, Yanyan; Li, Xin; Wang, Chunge; Zeng, Yaping; Yue, Guanghui; Chen, Qiang (Nano-Micro Letters, 2017)
Rechargeable lithium–oxygen batteries have been considered as a promising energy storage technology because of their ultra-high theoretical energy densities which are comparable to gasoline. In order to improve the electrochemical properties of lithium–oxygen batteries (LOBs), especially the cycling performance, a high-efficiency cathode catalyst is the most important component. Hence, we aim to demonstrate that CuCr2O4@rGO (CCO@rGO) nanocomposites, which are synthesized using a facile hydrothermal method and followed by a series of calcination processes, are an effective cathode catalyst. The obtained CCO@rGO nanocomposites which served as the cathode catalyst of the LOBs exhibited an outstanding cycling performance for over 100 cycles with a fixed capacity of 1000 mAh g−1 at a current density of 200 mA g−1. The enhanced properties were attributed to the synergistic effect between the high catalytic efficiency of the spinel-structured CCO nanoparticles, the high specific surface area, and high conductivity of the rGO. Highlights: 1 CuCr2O4@rGO nanocomposites were facilely synthesized using the hydrothermal method. 2 The CuCr2O4@rGO nanocomposites demonstrated an outstanding cycling performance for over 100 cycles with a fixed capacity of 1000 mAh g−1 at a current density of 200 mA g−1.